Effect of intravitreal bevacizumab on diabetic macular edema with hard exudates - Jeon S (Dove Medical Press, 2014)
Sohee Jeon, Won Ki LeeDepartment of Ophthalmology, Seoul St Mary’s Hospital, College of Medicine, The Catholic University of Korea, Seoul, KoreaBackground: We evaluated the efficacy of intravitreal bevacizumab on diabetic macular edema with subfoveal and perifoveal hard exudates.Materials and methods: Eleven eyes (11 patients) exhibiting diabetic macular edema with subfoveal and perifoveal hard exudates were included in this prospective, nonrandomized interventional pilot study. All patients were treated with monthly scheduled intravitreal bevacizumab injections for 6 months. Changes in the Early Treatment Diabetic Retinopathy Study best corrected visual acuity, amount of hard exudates on fundus photography, and macular edema detected by central subfield thickness on spectral domain optical coherence tomography after six serial injections, were assessed. The amount of hard exudates at each visit was evaluated as pixels in fundus photography, using an Adobe Photoshop program. Results: Ten of 11 patients completed follow-up. The mean Early Treatment Diabetic Retinopathy Study best corrected visual acuity was 59.9±5.7 letters (Snellen equivalent, 20/63) at baseline evaluation. The best corrected visual acuity exhibited no significant difference at month 6 compared with at baseline (57.9±6.0 letters or 20/70 at month 6; P=0.085). At month 6, mean central subfield thickness decreased from 370.4±56.5 to 334.6±65.0 µm (P=0.009). The mean amount of hard exudates increased from 4467.1±2736.1 to 6592.4±2498.3 pixels at month 6 (P=0.022). No serious adverse events occurred.Conclusion: Continuous intravitreal bevacizumab was found to have no benefit in visual acuity and amount of hard exudates, despite the improvement of macular edema at 6 months. Keywords: bevacizumab, diabetic macular edema, hard exudates